THE INTERACTION OF TEXT-TO-SPEECH AND LEARNING MOTIVATION ON PRE-SERVICE TEACHERS’ READING COMPREHENSION ABILITY - Sari, Maria Puspa
Some studies have proven that the utilization of text-to- speech has many good influences. However, learning motivation also affects learners’ reading comprehension ability. Meanwhile, good reading comprehension ability is a ‘must’ for learners especially pre-service teachers since they are supposed to be professional future teachers. This study aimed to investigate the impact of text-to-speech and learning motivation on pre-service teachers‟ reading comprehension ability. This research involved sixty preservice teachers who were at fourth semester of English Education Study Program of PGRI University of Palembang, and applied factorial design. Some results were revealed: (1) there was a statistically significant difference in reading comprehension ability between pre-service teachers who were taught using text-to- speech and those who were not; (2) there was no statistically significant interaction effect of text-to-speech and learning motivation on pre-service teachers‟ reading comprehension ability.